Da composição à estreia: uma análise das fontes musicográficas do Concerto para Piano e Orquestra de Octávio Maul (Orfeu, 2025)
This article concerns the tradition of Octávio Maul’s Concerto for Piano and Orchestra, composed in 1950 and premiered in 1951 at the Theatro Municipal of Rio de Janeiro. The research focuses on the analysis of the manuscript musicographic sources of the work, located at the National Library Foundation and the Alberto Nepomuceno Library of the School of Music at the Federal University of Rio de Janeiro (UFRJ). The examined sources—autographs and copies—reveal a continuous creative process, marked by textualrevisions and adaptations for performance. The study identifies substantial modifications in the score, such as tempo changes, rewritten instrumental passages, and supplementary performance markings, introduced by Maul possibly during preparatory rehearsals, reflecting his role as both composer and conductor. A critical analysis of the sources highlights the dynamic nature of the work and emphasizes the composer’s significance within the landscape of twentieth-century Brazilian concert music. Finally, the study points to the need for an edition that systematizes textual modifications and favors the circulation of the work in the contemporary repertoire.
Keywords: Octávio Maul; concerto for piano and orchestra; musicographic sources; textual tradition; brazilian music